Extraordinary enhancement of Néel transition temperature in nanoparticles of multiferroic tetragonal compositions of (1-x)BiFeO3-xPbTiO3 solid solutions - Upadhyay C.; Harijan P.K.; Senyshyn A.; Ranganathan R.; Pandey D. (My University, 2025)
The Néel temperature (TN) in conventional antiferromagnets (AFM) decreases with decreasing particle size. In contrast, we present here evidence for an exotic facet of multiferroicity, whereby one can raise the TN by more than 200K by decreasing the particle size. We illustrate this by taking the example of a tetragonal composition with x=0.5 in the solid solutions of (1-x)BiFeO3-xPbTiO3 (BF-xPT). We attribute it to the increase in the strength of the superexchange interaction via a decrease in the ferroelectric distortion in nanocrystalline powder of BF-0.5PT. The BF-0.5PT nanoparticles also exhibit exchange bias effect due to AFM core-FM shell type magnetic nanostructure. © 2015 AIP Publishing LLC.